Optimizing the Utilization of Village Land in Maintaining the Sustainability of Melikan Village Government - A. Masrich; Muhammad, Adji Suradji; Eka suswaini (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
Melikan is one of the best pottery producing villages. The ability to make pottery has been owned for generations and even had before prehistoric times. As a raw material in the manufacture of pottery, clay is the main element. So far, clay has been taken from crooked soil which is the right of village officials without any compensation to village officials. As a result, village officials did not benefit from the crooked land and there was natural damage that threatened the safety of villagers because of the puddles of former excavated soil. Through a qualitative research approach and supported by information from competent resource persons ranging from the Village Head, Village Consultative Board, Village Secretary, Village Apparatus, community leaders, youth leaders and religious leaders, it was obtained that there was a common desire to find a win-win solution. The win-win solution in question is that village officials get the right to get additional income and craftsmen get quality soil raw materials.